2019
DOI: 10.32718/nvlvet9429
|View full text |Cite
|
Sign up to set email alerts
|

Effect of “Amprolinsyl” and “Amprolium 22%” on morphological indices of blood of turkeys for eumeria invasion

Abstract: The article gives data on the influence of Amprolinsyl and Amprolium 22% on morphological parameters of blood after eumirioic invasion. It has been shown that after application of amprolium 22% for the treatment of turkeys infected with eumeria invasion, gradual normalization of hematological parameters of blood begins. Thus, at the 3rd day of treatment, the number of red blood cells increased, but remained 25.1% lower, and the hemoglobin level increased, but remained at 16.3% lower, compared with clinically h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
1
0
3
Order By: Relevance
“…Thus, the results of the study showed zinc poisoning of chickens even within 1-3 days led to damage to bone marrow cells. The cytoplasm of blood-forming and stromal cells of the bone marrow detects mostly signs of destructive processes, which are amplified as the duration and the dose of exposure increase [7]. At the same time, the structure of cell nuclei often gets changed in the bone marrow.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the results of the study showed zinc poisoning of chickens even within 1-3 days led to damage to bone marrow cells. The cytoplasm of blood-forming and stromal cells of the bone marrow detects mostly signs of destructive processes, which are amplified as the duration and the dose of exposure increase [7]. At the same time, the structure of cell nuclei often gets changed in the bone marrow.…”
Section: Discussionmentioning
confidence: 99%
“…Її рекомендують як корисний продукт у лікувальному та дієтичному харчуванні. Усі вказані чинники роблять цей вид м'яса доволі конкурентоспроможним порівняно із м'ясом інших видів птиці та забійних тварин [10,12,18].…”
Section: вступunclassified
“…Деякими вченими було встановлено складність патогенезу токсокарозу у тварин: розлади обміну речовин, порушення фізіологічних функцій організму, також було запропоновано різні способи лікування тварин за даної патології. Зокрема, досі залишається не виясненим питання про вплив токсокар та їх метаболітів на одну з важливих, захисних систем організму -антиоксидантну систему, завданням якої є підтримання балансу між інтенсивністю радикалоутворення та потребами організму у фізіолого-біохімічних аспектах дії радикалів кисню та їх похідних, а саме синтезу біологічно-активних речовин, регуляції проникності мембран (Stybel et al, 2019;Grymak et al, 2020;Varkholiak et al, 2021).…”
Section: вступunclassified